Analisis Penentuan Harga Pokok Produksi berdasarkan Metode Full Costing pada UMKM Sehi Kerpik - Shasa Yuni Nofiani; Kokom Komariah; Acep Syamsudin (IPM2KPE, 2022)
The purpose of this study was to analyze the allocation and calculation of the cost of production of cassava chips. This research method is a full costing method. The results show that the calculation of the cost of production using the full costing method does not include general and administrative costs in overhead costs, because these costs are a cost component in the company's income statement. In conclusion, the calculation of the cost of production as the basis for determining the selling price according to the full costing method is better in analyzing production costs Keywords: Full costing, Cost of Production